The Mirrors for Princes and Historical Codes of the Modern Leadership in the Middle East. - Altunok, Mustafa (European Journal of Social Science Education and Research, 2019)
The Mirrors for Princes are administrative texts of ancient history. These texts, referred to by different names, are considered to be important because they have a function of projection, for rulers of the period. And their importance is not limited by this, because of its features. Since criticism and suggestions for the next ruler also shows the people’s expectations, it is a reflection of the social and political characteristics of the period as well as texts. However, the Mirrors for Princes is not merely an object or the text to understand history or a period of time because these texts are elements of historical and social memory. From the text, written in the changing conditions and at different times, it can be understood that there were changing political and societal realities as well as unchanging elements. In this respect, the Mirrors for Princes can be considered not only an illumination of the past, staying in the dusty shelves of history, but also a relevant reflection that reaches to now. The main purpose of this study is to find out the secrets of leadership from this reflection. The main argument of this study is that this region has a historical code of the current leadership, which can be interpreted by the Mirrors for Princes. The backbone of the work depends on the interpretation and analysis of the Mirrors for Princes. This text was written in different times for different rulers; it raised powerful leaders from the Ottoman, Seljuk, Mongol, and Iranian societies. This research seeks to find out a different leader perception typology from commonalities despite social differences to different states and periodic variations. Considering that the Mirrors for Princes is an extensive literature, this study should be evaluated as a motivational tool for comprehensive successors.